Hubungan antara Academic Self-Confidence dengan Kejenuhan (Burnout) Belajar Siswa SMK Negeri 1 Indralaya Utara - Dewi, Riska Purnama; Yosef, Yosef; Harlina, Harlina (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2017)
he objective of this study was to find out if there was a correlation between academic self-confidence and students’ burnout of learning in Vocational School 1 Indralaya Utara. This study used quantitative approach with correlational method. The sample of this study was 69 students who chosen by using Solvin formula with fault level 10% out of 220 students. The sample was taken by using randomsampling technique. In collecting the data, academic self-confidence and burnout of learning scale questionnaires were used. In analyzing the data, pearson product moment formula was used. The result of the data analysis showed that there was a negative correlation between academic self-confidence and burnout of learning with correlation coefficient -0.77. Correlation coefficient -0.77 showed that there was a significant correlation between academic self-confidence and burnout in learning. The number of negative correlation coefficient (-) showed that there was a two tailed correlation that the higher an academic self-confidence the students had, the lower the students’ burnout of learning, in opposite, the lower an academic self-confidence the students had, the higher the students’ burnout of learning.